2013
DOI: 10.1002/bjs.9069
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of transanal total mesorectal excision

Abstract: Background: Laparoscopic resection of colorectal cancers is a safe alternative to open surgery. The conversion rate to open surgery remains fairly constant but is associated with increased morbidity. A new approach to the surgical excision of rectal cancer is transanal total mesorectal excision (TME), in which the rectum is mobilized peranally using endoscopic instruments. This feasibility study describes initial results with transanal TME. Conclusion:Transanal TME using the down-to-up principle is feasible. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 10 publications
3
85
0
4
Order By: Relevance
“…Neoadjuvant treatment was given to 81% of patients for locally advanced tumors (Table 1). 104,[107][108][109][110][111][112][113][114][115] Mean operative time was 272.5 min (range 120-460), with a mean of 2.8 abdominal trocars used (range 1-5), mean estimated blood loss of 77.8 mL (range 10-300), and mean LOS of 10.2 days (range . The overall intraoperative complication rate was 8.3%, including a 2.8% incidence of conversion to open surgery.…”
Section: Notes Transanal Rectosigmoid Resection: Clinical Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neoadjuvant treatment was given to 81% of patients for locally advanced tumors (Table 1). 104,[107][108][109][110][111][112][113][114][115] Mean operative time was 272.5 min (range 120-460), with a mean of 2.8 abdominal trocars used (range 1-5), mean estimated blood loss of 77.8 mL (range 10-300), and mean LOS of 10.2 days (range . The overall intraoperative complication rate was 8.3%, including a 2.8% incidence of conversion to open surgery.…”
Section: Notes Transanal Rectosigmoid Resection: Clinical Trialsmentioning
confidence: 99%
“…All TME specimens were complete, and 94% had negative margins (Tables 2,3). 104,[107][108][109][110][111][112][113][114][115] …”
Section: Notes Transanal Rectosigmoid Resection: Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The macroscopic quality of TME was documented in all published reports, except in study of Wolthuis et al [103] and has been reported as ''intact'' [110] , ''adequate'' [111,112] , ''satisfactory'' [104,113] , or ''complete'' [11,12,106,107,111,114] .…”
Section: Oncological Outcomesmentioning
confidence: 99%
“…Atallah et al published the first series of TAMIS-TME in 20 patients with rectal cancer [2]. Although evidence on the efficacy of TAMIS-TME in rectal cancer has been accumulating [3,4]. there is scarce data on its use in inflammatory bowel disease.…”
Section: Introductionmentioning
confidence: 99%